Cu5FeS4 quantum dots as a single-component photo-assisted electrocatalyst for efficient hydrogen evolution. Issue 4 (5th January 2023) - Zhang, Dongxu; Liu, Yanhong; Li, Longhua; Li, Di; Jiang, Tianyao; Huang, Hui; Jiang, Deli; Kang, Zhenhui; Mao, Baodong
Abstract : Cu5 FeS4 quantum dots as a single-component photo-assisted electrocatalyst for efficient hydrogen evolution reaction superior to Pt/C. Abstract : Photo-assisted electrocatalytic (P-EC) hydrogen evolution reaction (HER) has attracted extensive attention by directly integrating the photo- and electroactive materials, exhibiting dramatically improved activity and kinetics upon light irradiation. In this work, an efficient single-component P-EC catalyst was developed by growing Cu5 FeS4 quantum dots (QDs) on nickel foam (NF) in situ toward the concept approval of dual function integration in one particle. The optimized Cu5 FeS4 /NF catalyst displays a dramatic overpotential decrease from 118 mV to 52 mV at 10 mA cm −2 for HER under light, exceeding that reported for all transition metal sulfides. Moreover, to reach 100 mA cm −2, it requires an overpotential of 242 mV, superior to commercial Pt/C (256 mV). The excellent P-EC performance is attributed to the effective integration of the induced photovoltage and promoted active sites in Cu5 FeS4, as observed by the photoinduced flat-band potential increase and impedance decrease. Transient photovoltage spectroscopy indicated the promoted charge extraction kinetics in Cu5 FeS4 with Fe incorporation. DFT calculations confirm the decreased adsorption free energy of H* and promoted HER kinetics on Cu5 FeS4 with light. This work provides an effective fabrication strategy for the synergy of photo- and electrocatalysis in one particle. Understanding the mechanism also provides an interesting inspiration for integrated photoelectrocatalysis in other more challenging fields, such as carbon dioxide and nitrogen reduction.